Graded Roll-to-Roll Slot Die Coating for High-Throughput Catalyst Layer Studies - Pätzold, George; Maier, Maximilian; Löttert, Lukas; Freiberg, Anna T.S.; Thiele, Simon; Dworschak, Dominik (ChemElectroChem, 2025)
Fuel cells play a key role in the energy transition to renewable resources. Many of these systems are based on substrates coated with thin layers containing catalyst, ionomer or support material like carbon. In order to experimentally define the optimal catalyst layer configuration, one must do step-by-step variations of its components. Currently this must be done in several single coating experiments. Here we present a tabletop roll-to-roll (R2R) slot die coating setup for producing wet film graded catalyst layers for high-throughput loading studies. In the presented work we perform a loading study for proton exchange membrane fuel cell (PEMFC) cathodes where all investigated loadings result from one single coating. The wet film thickness is measured during the continuous coating process via in-line confocal sensors and is correlated by area X-ray fluorescence (XRF) scans. Small sections of the graded catalyst layer coatings were tested in a full cell PEMFC with a 5 cm2 active area. The known loading dependency of PEMFC performance was shown and compared to previous loading studies. The results show the successful fabrication of the graded layer which can be used for both, to facilitate materials development and to increase cell performance in stacks.
CRIS-Team Scopus Importer:2025-03-28
Keywords: catalyst loading; fuel cells; high-throughput screening; in-plane gradient; R2R